PENAMBAHAN BUAH NANASDALAM PEMBUATANVELVA WORTEL - Tampubolon, Ratih Helen Sri Hartati; Yusmarini, Yusmarini; Johan, Vonny Setiaries (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research was to get the best formulationof velvacarrot with additional pineapple. This research was used Completely Randomized Design (CRD) with five treatments and four replication which followed by Duncan’s New Multiple Range Test (DMNRT) atlevel of 5%. The treatments were WN1 (puree carrot 100%), WN2 (puree carrot 80% : puree pineapple 20%), WN3 (puree carrot 70% : puree pineapple 30%), WN4 (puree carrot 60% : puree pineapple 40%) and WN5 (puree carrot 50% : puree pineapple 50%). The results showed that the concentration of puree carrot and puree pineapple in making velvasignificantly affected to degrees of overrun, acidity (pH), melting time, crude fiber content, and assessment sensory (descriptive and hedonic). The best treatment of making velvawas WN5 with overrun 27.75%, pH 4.16, melting time 16.62 minutes, crude fiber content 1.29% and organoleptic scores of WN5are 3.04 (colour), 2.56 (flavour), 2.44 (taste), 3.52 (texture) and overall (2.77). Keywords: velva, carrot, pineapple.